Pengaruh Profitabilitas, Ukuran Perusahaan, dan Leverage Terhadap Nilai Perusahaan Manufaktur - Fasya, Muhammad Ardian; Bakhtiar, Muhammad Ilham; Amaroh, Siti (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2025)
The purpose of this research is to find out the Value of Companies that have been listed on the Indonesia Stock Exchange (IDX) which are affected by Profitability, Sales Distribution, Leverage during the 2020-2022 period. The population in this study are manufacturing companies listed on the IDX in the period 2020-2022. This study used a sample using purposive sampling method so that out of 15 companies, 13 manufacturing companies were found to be able to fulfill the model used as an exploratory test. The SPSS 26 program was used to perform multiple linear regression analysis for this study. The findings show that Firm Value is not significantly affected by Profitability and Leverage. Meanwhile, company size has a significant effect on the share capital structure of manufacturing companies listed on the IDX for the 2020-2022 period.